Analytical Method and Synthetic Method in Marburg Neo-Kantianism - Pelegrín, Laura (Studia Kantiana, 2023)
Kant distinguishes between two methods in philosophy: the analytical method and the synthetic method. According to the analytical method, philosophy starts from a given fact to find its conditions of possibility. On the contrary, the synthetic method starts from an obscure and confused representation to provide clarity and distinction to each concept in order to show its necessary relation with other concepts. Marburg Neo-Kantianism holds that philosophy must begin with the fact of science. These claims have led numerous commentators to identify the Neo-Kantian method as a regressive method. I will show that, according to Paul Natorp’s approach, the progressive method is the fundamental method of philosophy while the analytical method is a second step in the investigation.